Physiotherapists' management of challenging situations in guiding people with rheumatoid arthritis to health-enhancing physical activity. (2nd January 2019) - Nessen, Thomas; Opava, Christina H; Martin, Cathrin; Demmelmaier, Ingrid
ABSTRACT: Objectives : To explore strategies used by physiotherapists (PTs) in guiding people with rheumatoid arthritis to health-enhancing physical activity (HEPA) in a group setting during a 1-year intervention study. Methods : Exploratory design with qualitative video analysis performed in three steps. Eleven female PTs were video recorded while leading support group sessions aiming at facilitating HEPA (twice-weekly exercise sessions at public gyms and 150 weekly minutes of moderately intense aerobic physical activity). Results : Three categories of challenging situations emerged. They occurred when the HEPA intervention participants reported barriers to performing physical activity, when they neglected to use the planning tool for physical activity as intended in the program, and when they received negative results from physical capacity tests. PTs used different strategies to manage these challenges, with main focus either on information-giving, corresponding to a traditional health professional approach, or utilizing group resources by organizing participation. Conclusions : This study provides detailed descriptions of PTs' clinical behavior in video-recorded sessions. The results imply that motivated PTs can, despite their biomedical and practitioner-focused training, learn to adapt their communication strategies to different situations, altering between traditional information-giving and utilizing group resources by organizing participation.